Commentary on foresight and trade-off analysis for agriculture and food systems - Wiebe, Keith D.; Prager, Steven D. (Oxford University Press, 2021)
The papers and ideas on foresight and trade-off analysis presented in this issue are very timely. They come as our agriculture, food, and related resource systems are experiencing severe shocks (immediate as well as longer term) that call for unprecedented responses under a high degree of uncertainty. At the same time, a key part of the international agricultural research system is undergoing a fundamental restructuring that challenges us with both need and opportunity to rethink research priorities to inform decision making and improve agriculture and food system outcomes. These papers offer insights into how foresight and trade-off analysis can help us meet the complex, integrated changes that we are currently facing—and will continue to face for many years to come.